2013
DOI: 10.1371/journal.pone.0069311
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Guided Cervical Selective Nerve Root Block with the Dyna-CT: Initial Experience of Three-Dimensional Puncture Planning with an Ex-Vivo Model

Abstract: BackgroundCervical selective nerve root block (CSNRB) is a well-established, minimally invasive procedure to treat radicular cervical pain. However, the procedure is technically challenging and might lead to major complications. The objective of this study was to evaluate the feasibility of a three-dimensional puncture planning and two-dimensional laser-guidance system for CSNRB in an ex-vivo model.MethodsDyna-CT of the cervical spine of an ex-vivo lamb model was performed with the Artis Zee® Ceiling (Siemens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…For example, Freundt et al used iGuide with DynaCT for cervical selective nerve root block in an ex-vivo lamb model and found that compared to CT-guided procedures, they required significantly fewer attempts in accessing the target. 7 Exposure to ionizing radiation remains a concern for fluoroscopy-guided procedures as for CT-guided procedures and this risk must be balanced carefully with the benefits of precise needle guidance. Further study comparing relative radiation exposures for these two approaches is needed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Freundt et al used iGuide with DynaCT for cervical selective nerve root block in an ex-vivo lamb model and found that compared to CT-guided procedures, they required significantly fewer attempts in accessing the target. 7 Exposure to ionizing radiation remains a concern for fluoroscopy-guided procedures as for CT-guided procedures and this risk must be balanced carefully with the benefits of precise needle guidance. Further study comparing relative radiation exposures for these two approaches is needed.…”
Section: Discussionmentioning
confidence: 99%
“…This enables a myriad of imaging-guided interventional procedures within the angiography suite (eg, percutaneous spine interventions, complex peripheral vascular interventions). 17–20 Recently, use of the CB-CT-guided technique has been reported for the placement of external ventricular drains within the angiography suite. 4 …”
Section: Discussionmentioning
confidence: 99%
“…The feasibilities of this puncture planning and guidance system had been previously demonstrated in selective cervical nerve root block, 12 percutaneous kidney puncture, 13 and hepatic tumor ablation 13 based on ex vivo animal models and real patients. Its application in the brain was only recently demonstrated on 6 patients with cerebrovascular ischemia for external ventricular drainage.…”
mentioning
confidence: 96%